Research progress on the treatment and nursing of ingrown toenails paronychia (嵌甲型甲沟炎的临床治疗及护理进展) - DENG Yiou (邓翼鸥); CHEN Yuguo (陈玉果) (中西医结合护理)
The ingrown toenails paronychia is a common nail problem occurring when the nail plate grows laterally into the periungual skin. It may cause hypertrophy of the nail folds tissues and purulent granuloma. At present, the clinical treatment of ingrown toenails paronychia mainly includes conservative treatment and surgical treatment. Appropriate treatment methods should be selected according to the demands of patients and the clinical manifestations of nail inlay. In addition, enhancement of prevention, removing potential causes and treating according to the nail inlay are helpful to reduce the recurrence rate and achieve relatively sound clinical efficacy. This review summarizes the clinical treatment and nursing progress of ingrown toenails paronychia, in order to provide reference for improving treatment efficacy and nursing quality. (嵌甲型甲沟炎是由于足趾两侧皮肤与皮下组织挤向趾甲或趾甲边缘压入甲沟软组织所致, 可引起甲缘外侧组织增生肥大和化脓性肉芽肿。目前, 临床上治疗嵌甲型甲沟炎主要包括保守治疗和手术治疗。临床上应根据患者的诉求以及嵌甲的临床表现选择合适的治疗手段, 同时重视预防, 去除诱因, 根据甲类型分别施治, 从而有效降低复发风险, 得到相对满意的临床疗效。本文综述嵌甲型甲沟炎的临床治疗及护理进展, 旨在为提高临床疗效及护理质量提供参考。)